1998
DOI: 10.1080/1066892980220302
|View full text |Cite
|
Sign up to set email alerts
|

Managing Scarce Resources in the Community College: Strategies for the Department Chair

Abstract: In recent years, the community college and higher education in general has witnessed a decrease in funding at the federal, state, and local levels. Community colleges, in turn, have called on the departmental level administrator to deal with the problem of real or impending budget reductions. Therefore, fiscal management has become one of the primary tasks of these mid-level administrators. The present study examined how specific strategies might be utilized by department chairs to better manage scarce resourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It was found that collaborative leadership is the most effective style for a community college chair and that community college chairs experience challenges in leading curriculum (Albashiry et al, 2015;Eager Sirkis, 2011). Additional older studies include community college chair perceptions of financial issues (Miller & Seagren, 1997), faculty empowerment through leadership (McArthur, 2002), mid-level management development (Spangler, 1999), and managing resources (Miller, 1998). Each of these studies profiles the challenges and limitations of being a community college chair, which was also consistent with findings of more recent surveys (Paape et al, 2021;Prentice & Guillaume, 2021) In small sample of approximately 34 participants, it was found that community college department chairs may typically enter the position in their mid-40s, remain in the role at least 5 years, hold master's degrees, and are equally likely to hold any of the three academic professor ranks (Prentice & Guillaume, 2021).…”
Section: Community College Department Chairsmentioning
confidence: 99%
“…It was found that collaborative leadership is the most effective style for a community college chair and that community college chairs experience challenges in leading curriculum (Albashiry et al, 2015;Eager Sirkis, 2011). Additional older studies include community college chair perceptions of financial issues (Miller & Seagren, 1997), faculty empowerment through leadership (McArthur, 2002), mid-level management development (Spangler, 1999), and managing resources (Miller, 1998). Each of these studies profiles the challenges and limitations of being a community college chair, which was also consistent with findings of more recent surveys (Paape et al, 2021;Prentice & Guillaume, 2021) In small sample of approximately 34 participants, it was found that community college department chairs may typically enter the position in their mid-40s, remain in the role at least 5 years, hold master's degrees, and are equally likely to hold any of the three academic professor ranks (Prentice & Guillaume, 2021).…”
Section: Community College Department Chairsmentioning
confidence: 99%